Cranial Nerve Anatomy Using a Modular and Multimodal Radiologic Approach - Christopher M. Lack; Joseph Pena; Elizabeth X. L. Grubb; E Shen; Kevin D. Hiatt; Marc D. Benayoun; Fredrick S. Jones; Thomas G. West (Association of American Medical Colleges, 2022)
Introduction Medical students often struggle with learning cranial nerve anatomy. Typically, cranial nerve anatomy is taught using didactic lectures and textbook illustrations, often leaving students frustrated. Methods We developed a multimodal radiologic approach to teaching cranial nerve anatomy. First, 150 students were presented with carefully curated preclass material from which to prepare. Next, they received a didactic lecture that was recorded for them to revisit on their own time. Last, students worked in groups in a lab setting with expert radiologists to identify the cranial nerves and related anatomy and learn about some basic pathophysiology. We used a pretest and posttest to examine the effectiveness of our teaching methods and a survey to measure students' satisfaction. Results Student knowledge of cranial nerve structure was significantly improved after our module, with quiz scores increasing from 4.6 to 6.8 out of 9.0 (p < .001). In addition, students reported feeling more confident in their knowledge of the material and offered high satisfaction scores. Discussion The breadth of knowledge covered during the preclinical training years continues to expand despite stable or even contracted durations of training, requiring knowledge to be delivered in an ever more efficient manner. Ultimately, the multimodal pedagogy used by our resource leads to students who are more confident and engaged in their learning, resulting in increased knowledge.